Application of Total Productivity Model within Croatia Airlines - Željko Radačić; Mirko Tatalović; Ivan Mišetić; Ivan Furlan (Promet - Traffic&Transportation, 1970)
By defining and selecting adequate factors of the total productivitymodel and by assigning specific relevance of each factor,the initial preconditions for the analysis and monitoring ofthe model application efficiency within the Croatia Airlinesbusiness policy have been established. Since the majority of theanalyzed factors have realized a more intensive growth thanplanned, the business year 2004 can be assessed as the mostsuccessful one in the Croatia Airlines history. Consequently,the difference related to the productivity indicators of the Associationof European Airlines has been reduced, particularly theaircraft productivity with remnant of 5 to 10 percent, and theproductivity of the employees with a remnant of 15 to 20 percent,and the productivity of fuel expressed as quantity at AEAlevel, and expressed as value below that level. Finally, althoughthere is no expressed correlation between the quantitative productivityindicators and business profitability, the highest realizednet profit since the foundation of Croatia Airlines fullysupplements the solid level of the comparison indicators, confirmingits complete readiness and maturity to join the Star Alliance.